2019
DOI: 10.1039/c9cc07840a
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-catalyzed electrochemical reductive decarboxylative coupling of N-hydroxyphthalimide esters with quinoxalinones

Abstract: The first example of electrochemically enabled, NiCl2-catalyzed reductive decarboxylative coupling of N-hydroxyphthalimide esters with quinoxalinones was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…After that, the generated radical intermediate 14 would be oxidized at the anode to yield the protonated product (Figure 9C). Around the same time, Zeng, Xu, and co‐workers reported an electrochemical decarboxylative coupling of NHP esters with quinoxalinones for the synthesis of 3‐alkylated quinoxalinones by using nickel as the mediator [23] …”
Section: Sequential Paired Electrolysismentioning
confidence: 99%
“…After that, the generated radical intermediate 14 would be oxidized at the anode to yield the protonated product (Figure 9C). Around the same time, Zeng, Xu, and co‐workers reported an electrochemical decarboxylative coupling of NHP esters with quinoxalinones for the synthesis of 3‐alkylated quinoxalinones by using nickel as the mediator [23] …”
Section: Sequential Paired Electrolysismentioning
confidence: 99%
“…In general, NHP esters are versatile Csp 3 alkyl radical precursors and show tolerance with various functional groups. In the series of electrochemical metal‐catalyzed reactions, Zeng et al [18] . reported the first example of nickel‐catalyzed electrochemical decarboxylative coupling of NHP esters with 2‐quinoxalinones, yielding the various Csp 3 −Csp 2 coupled products under mild conditions (Scheme 4).…”
Section: Electrochemical Decarboxylative C−c Bond Formationmentioning
confidence: 99%
“…[16] However,s trong chemical oxidants such as TBHP and K 2 S 2 O 8 were neededf or the generation of alkyl radicals from alkyl radical precursors and these alkyl radical precursors were not compatible with functional group tolerances. [17] In general, NHP esters are versatile Csp 3 alkyl radicalp recursors ands how tolerance with various functional groups.I nt he series of electrochemical metal-catalyzed reactions, Zeng et al [18] reported the first example of nickel-catalyzede lectrochemicald ecarboxylative coupling of NHPe sters with 2-quinoxalinones, yielding the various Csp 3 ÀCsp 2 coupled products under mild conditions (Scheme 4). Under the optimized reaction conditions, NHP protected primary,s econdary,a nd tertiary aliphatic carboxylic acids afforded the various 3-alkylated quinoxalinones (6a-c)i ng ood to excellent yields.…”
Section: Electrochemical Decarboxylative Càcb Ond Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeng and co-workers developed a method of Ni-catalyzed electrochemical reductive coupling of NHP esters with quinoxalinones for the synthesis of 3-alkylated quinoxalinones ( Lian et al., 2019 ). Reaction condition optimization demonstrated that graphite felt and nickel foam were the optimal electrode materials and reactions were conducted in an undivided cell with Et 3 N as the sacrificial reductant.…”
Section: Electrochemical Nickel Catalysismentioning
confidence: 99%